RANCANG BANGUN SISTEM INFORMASI KLINIK BERBASIS WEB DENGAN LARAVEL - Arif Malik Priyandri; Efmi Maiyana (Universitas Methodist Indonesia, 2025)
Previously, patient, doctor, and examination data management at Lestari Mandiri Clinic was still done manually, which often caused delays in recording and data errors. To overcome these problems, a web-based clinic information system was developed using the Laravel framework and MySQL database. The system development went through several stages, namely needs analysis, system design, implementation, testing, and maintenance. This system is designed with a simple and easy-to-use interface to suit the needs of clinic staff. The test results showed that the system can run well and fulfill the main functions such as recording patient data, managing doctors, and examination results. In addition, this system can also be further developed by adding features such as automatic reports, control schedule reminders, and drug stock management. With this information system, the clinic administration process becomes more efficient, accurate, and supports better service to patients.